2005
DOI: 10.1542/peds.2004-1688
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Evaluation of How Many Infants With Permanent Hearing Loss Pass a Two-Stage Otoacoustic Emissions/Automated Auditory Brainstem Response Newborn Hearing Screening Protocol

Abstract: If all infants were screened for hearing loss using the 2-stage OAE/A-ABR newborn hearing screening protocol currently used in many hospitals, then approximately 23% of those with PHL at approximately 9 months of age would have passed the A-ABR. This happens in part because much of the A-ABR screening equipment in current use was designed to identify infants with moderate or greater hearing loss. Thus, program administrators should be certain that the screening program, equipment, and protocols are designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(133 citation statements)
references
References 18 publications
6
123
1
2
Order By: Relevance
“…This fact would mean that in a screening programme using TEOAE alone, there would be a high number of referrals. The specificity can possibly be improved by repeating the TEOAE test at least once in those who fail it the first time [8].…”
Section: Aabrmentioning
confidence: 99%
“…This fact would mean that in a screening programme using TEOAE alone, there would be a high number of referrals. The specificity can possibly be improved by repeating the TEOAE test at least once in those who fail it the first time [8].…”
Section: Aabrmentioning
confidence: 99%
“…1 Before the implementation of universal newborn hearing screening, most children with these minimal degrees of hearing loss were not identified until they were school aged. 7 Although not all infants with MBHL or UHL will be identified in the newborn period, 8 many audiologists find themselves in the challenging role of counseling families about the potential effect of these losses and informing them about available hearing technologies. Although the choice to fit infants with moderate or greater degrees of bilateral hearing loss has been standard practice for most clinicians, the decision of whether or not to fit hearing technology on children with MBHL or UHL is less clear.…”
Section: Amplification Considerations For Children With Minimal or MImentioning
confidence: 99%
“…31,32 Although our current screening technologies (eg, automated auditory brainstem response [AABR] and otoacoustic emission [OAE] testing) are effective at identifying moderate or greater degrees of hearing loss, a significant proportion of infants with milder degrees of hearing loss may be missed. Johnson et al 8 found that a high proportion of infants with later confirmed bilateral or unilateral mild permanent hearing loss were not identified (using a pass or refer criteria) by a 2-step, 2-technology hearing screening protocol (OAE followed by AABR testing). Although it is possible that some of these losses progressed or had onset after the newborn period, it is reasonable to assume that many of these were missed by the screen.…”
Section: Current Practice Policiesmentioning
confidence: 99%
“…Usually a hearing screening programme after two referred step orders a global audiological assessment for a refer newborn [30]; the originality of this experimental protocol is that the infants that FAIL without audiological risk factor, below to group G3 and most likely to have a high number of refer, underwent screening 2 weeks later, for a maximum of four times. This measure, without additional cost since it was used the same instrumental, allowed us to lead the total number of newborns admitted to comprehensive audiologic assessment from 51 to 31 newborns with a percentage value of 0.91% that is more lower than those of 4% suggested by JCIH; therefore the number of false positives resulted 21 corresponding to 0.62% with a final specificity value of 99.4 AE 0.4% as showed in Table 2.…”
Section: Discussionmentioning
confidence: 99%